Pembentukan Identitas Diri Siswa melalui Interaksi Simbolik dalam Pembelajaran Seni Tari di SMA Diponegoro 1 Purwokerto - Diasworo, Oeky; Hanif, Muh. (VISA: Journal of Vision and Ideas, 2025)
Herbert Blumer is applied in the formation of students' self-identity through symbolic interaction in dance learning at SMA Diponegoro 1 Purwokerto. In addition, this study also wants to know how dance learning can help students face the challenges of their identity development. Third, this study aims to understand how the application of symbolic interaction can improve students' understanding of themselves and their roles in society. Using the symbolic interaction theory of Mead and Blumer, this study analyzes how students form their identities through the interaction and interpretation of symbols in the context of dance learning. Dance is not only a cultural expression, but also a tool for understanding and interpreting cultural symbols. The interview method was chosen as the right step to collect data relevant to the focus of this study, because interviews allow researchers to explore the experiences and in-depth perspectives of students and dance teachers. This study is a descriptive qualitative study, using interviews to collect data from dance teachers and students who have experience in dance learning at SMA Diponegoro 1 Purwokerto. In addition, an analysis of curriculum documents and dance lesson plans was carried out to provide a broader context and ensure the validity of the research findings. Thus, the results of this study are expected to be applied in dance learning in other schools, especially if there are obstacles in the learning process. The results of this study will certainly add general insight to all educational institutions in Indonesia, both at SMA Diponegoro 1 Purwokerto and other schools. This shows that dance learning is not only about technical skills but also about a broader understanding and appreciation of culture, making an important contribution to the formation of students' self-identity and their understanding of their role in society.